2012
DOI: 10.4137/cmc.s4324
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin: A Review of the Pharmacology and Clinical Effectiveness in Cardiovascular Disease

Abstract: Rosuvastatin is a new generation HMG-CoA reductase inhibitor which exhibits some unique pharmacologic and pharmacokinetic properties. It has low extrahepatic tissue penetration, low potential for CYP3A4 interactions and substantial LDL-C lowering capacity and therefore has distinct advantages. We conducted a Medline literature search to identify rosuvastatin papers published in English. In this review, we outline the pharmacology of rosuvastatin, highlighting its efficacy and safety. We also review the major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 98 publications
(154 reference statements)
1
105
0
3
Order By: Relevance
“…However, the administration of rosuvastatin for 14 days did not significantly influence the serum activity levels of the enzymes compared with the control group. Previous studies demonstrated that rosuvastatin may occasionally induce alterations in hepatic enzyme activity levels; however, these changes infrequently caused liver failure (4,6). In the controlled clinical trials of rosuvastatin, the incidence of clinically significant ALT increases was low, and similar across all doses (0.1-0.5%), and these elevations were dose-dependent (24,25).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, the administration of rosuvastatin for 14 days did not significantly influence the serum activity levels of the enzymes compared with the control group. Previous studies demonstrated that rosuvastatin may occasionally induce alterations in hepatic enzyme activity levels; however, these changes infrequently caused liver failure (4,6). In the controlled clinical trials of rosuvastatin, the incidence of clinically significant ALT increases was low, and similar across all doses (0.1-0.5%), and these elevations were dose-dependent (24,25).…”
Section: Discussionmentioning
confidence: 95%
“…In short-term placebo-controlled trials, transient proteinuria was detected in 0.1% patients receiving rosuvastatin at a dose of 40 mg. Patient elevated proteinuria levels during rosuvastatin therapy were generally resolved spontaneously later during the trial (4,6,9). In addition, long-term data indicates that rosuvastatin appears to marginally improve renal function (6).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations